Quality of biogenic carbon dioxide stream from biogas plants including analytical method development - Karine Arrhenius; Sandra Hultmark; Iris de Krom; Luuk Meijer; Emma Henderson; Janneke van Wijk (Journal of CO2 Utilization)
The capture, use and storage of biogenic CO2 from the biogas sector contributes to environmental benefits by reducing the overall greenhouse gas emissions. In several plants, CO2 separated in the biogas upgrading process is captured and processed. Depending on the composition, some level of purification is needed before the biogenic CO2 can be used, for example, in the food industry. In this article, we first present novel or adapted analytical methods which are both cost-effective and reliable to assess the purity of CO2 streams. These methods concern not only species that are currently regulated in different standards but also allows for an extensive overview of the overall gas composition. The methods are then applied to samples of CO2 stream collected from different biogas plants located in Sweden. Results from this campaign are presented together with some conclusions regarding the need to further purify the stream so the CO2 even fulfill the most stringent requirements such as those set by the food industry. The need for purification concerns only a few species: water, methane, oxygen, nitrogen (for all samples), and hydrogen sulfide (in two cases). VOCs found specifically when the plants digest food wastes may also require a purification step, however, only some of these compounds are currently regulated.